👤

Answer :

Answer:

x=-1

Step-by-step explanation:

First we can square both sides to remove the square roots:

[tex](\sqrt{x+7})^{2} +(\sqrt{x+2})^{2} = (\sqrt{6x+13})^{2}[/tex]

Simplify:

[tex]x+7+x+2=6x+13[/tex]

Now we simplify further:

[tex]2x+9=6x+13[/tex]

Now we subtract 13 from both sides:

[tex]2x+9-13=6x+13-13[/tex]

Simplify:

[tex]2x-4=6x[/tex]

Subtract 2x from both sides:

[tex]2x-4-2x=6x-2x[/tex]

Simplify:

[tex]-4=4x[/tex]

Divide both sides by 4:

[tex]\frac{-4}{4} = \frac{4x}{4}[/tex]

Simplify:

-1=x

x=-1